Analyzing The Factors Affecting Employee Performance at LKP Bina Teknologi - Burhanudin, Burhanudin; Suwandi, Yudi Wahyudin (TechTalent & Business Review, 2025)
Employee performance is an important factor in determining the success of an organization. The achievement of optimal performance is greatly influenced by the effectiveness of leadership style, the strength of the organizational culture, and the level of work discipline. In practice, there are still many organizations that face challenges in the form of ineffective leadership, a work culture that has not been well formed, and discipline that has not been consistent, resulting in a decrease in employee productivity. Based on this phenomenon, this study aims to analyze the influence of leadership style, organizational culture, and work discipline on employee performance, both partially and simultaneously. This study uses a quantitative approach with a survey method, where data is collected through the distribution of questionnaires to respondents who are employees in an organization. Data analysis was carried out using the path analysis method to determine the direct and indirect influence between variables, as well as to test the level of significance of the relationship that occurred. The results of the study show that leadership style, organizational culture, and work discipline each have a positive and significant effect on employee performance. Among the three, organizational culture is the factor that contributes the most to improving performance. Simultaneously, these three variables interact with each other and create a conducive work environment, which encourages employee motivation, responsibility, and commitment in achieving organizational goals. These findings confirm that employee performance improvement can be achieved through the application of an effective leadership style, the formation of a strong organizational culture, and the consistent application of work discipline.